2023
DOI: 10.3390/ijms24021720
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity Disrupts Nuclear Factor κB Signaling and Impairs Murine Dendritic Cell Phenotype and Function

Abstract: During spaceflights, astronauts face different forms of stress (e.g., socio-environmental and gravity stresses) that impact physiological functions and particularly the immune system. In this context, little is known about the effect of such stress on dendritic cells (DCs). First, we showed that hypergravity, but not chronic ultra-mild stress, a socio-environmental stress, induced a less mature phenotype characterized by a decreased expression of MHCII and co-stimulatory molecules. Next, using the random posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The authors demonstrated that non-matured RPM-exposed BMDCs exhibited a more immature phenotype, compared to the control BMDCs. These data correlated with an impaired ability of BMDCs to express pro-inflammatory cytokine transcripts as shown in Figure 3A of [ 130 ]. A deregulation of DC function is likely responsible for inducing immune deregulation during spaceflight [ 130 ].…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…The authors demonstrated that non-matured RPM-exposed BMDCs exhibited a more immature phenotype, compared to the control BMDCs. These data correlated with an impaired ability of BMDCs to express pro-inflammatory cytokine transcripts as shown in Figure 3A of [ 130 ]. A deregulation of DC function is likely responsible for inducing immune deregulation during spaceflight [ 130 ].…”
Section: Resultsmentioning
confidence: 60%
“…These data correlated with an impaired ability of BMDCs to express pro-inflammatory cytokine transcripts as shown in Figure 3A of [ 130 ]. A deregulation of DC function is likely responsible for inducing immune deregulation during spaceflight [ 130 ].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations